2016
DOI: 10.1111/apa.13516
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of tigecycline shows that it may be an option for children with severe infections

Abstract: Our findings suggest that tigecycline may be an option for children with severe infections. However, more prospective, controlled trials are required to objectively evaluate the efficacy and safety of tigecycline in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 22 publications
4
25
1
Order By: Relevance
“…In our series, TGC was used in combination with other antibacterial agents in all cases. This is in line with recent reports on TGC use in the treatment of critically ill children . In a cohort study on 661 adults with pneumonia caused by KPC‐producing K pneumoniae , the survival improved only when at least two in vitro active antimicrobial agents were included in the regimen .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In our series, TGC was used in combination with other antibacterial agents in all cases. This is in line with recent reports on TGC use in the treatment of critically ill children . In a cohort study on 661 adults with pneumonia caused by KPC‐producing K pneumoniae , the survival improved only when at least two in vitro active antimicrobial agents were included in the regimen .…”
Section: Discussionsupporting
confidence: 88%
“…This is in line with recent reports on TGC use in the treatment of critically ill children. 15,32 In a cohort study on 661 adults with pneumonia caused by KPC-producing K pneumoniae, the survival improved only when at least two in vitro active antimicrobial agents were included in the regimen. 33 We also found low mortality in children with BSI when treated with TGC.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all of the available data regarding the use of tigecycline in infants and children younger than 8 years derive from small case series collected retrospectively. [3][4][5][6][7]10 Although optimal dosage has not been defined, the usual dose reported in different case series ranged from 1 to 2 mg/kg every 12 hours. 1 In a case report of 12-month old liver transplant recipient with XDR Acinetobacter baumannii bacteremia, it was found that a dose of 1 mg/kg every 12 hours (without loading dose) provided similar drug exposure (area under the curve, AUC) with adult and children aged 8 to 11 years old.…”
Section: Discussionmentioning
confidence: 99%
“…In different case series, the loading dose has been administered in the most pediatric patients but in infant patients it was not generally given. [3][4][5][6][7]10 All patients in this case series were preterm infants, so the loading dose was not given due to the lack of pharmacokinetics and pharmacodynamics analysis in this population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation